Phosphoprotein Phosphatase Activity Associated with Estrogen-Induced Protein in Rat Uterus - Vokaer, Alain (1974)
Estrogen-induced protein was purified from rat uteri and assayed for several enzymatic activities involved in the metabolism and action of cyclic nucleotides. No adenylate and guanylate cyclase (EC 4.6.1.1 and 4.6.1.2, respectively), protein kinase (EC 2.7.1.33), and cyclic nucleotide binding activities could be demonstrated in three independent preparations of the protein. However, all three preparations exhibited significant phosphoprotein phosphatase activity (EC 3.1.3.16) on phosphorylated protamine and histones F1. This activity is optimal at neutral pH, inhibited by Zn(++), and unaffected by cyclic AMP or cyclic GMP.